A percepção ambiental como instrumento de apoio de programas de educação ambiental da Estação Ecológica de Jataí (Luiz Antonio, SP) - Fiori, Andréia de (2006)
The actual development model based on the conversion of natural habitats into agricultural landscapes has been considered the major environmental impact resulting from anthropogenic activities and constitutes a constant menace to the biodiversity and it could be related to the perception of the society about the environmental problem and the regional producing activities. In this sense, the investigation of the environmental perception constitutes an indispensable tool for research projects that approach the relationships human-environmental and environmental management. The main objective of this work was environmental perception investigation of the fundamental educational of three surrounding places (Luiz Antônio, Rincão, Santa Rita do Passa Quatro and São Simão, SP) to the Ecological Station of Jataí (EEJ), Luiz Antônio, SP The results of the present study allowed to observe that the most of the educational ones conceives the environment as pure nature, restricted to the biophysical components, in that the human being is just an observer and the perception of the concept of Environmental Education presents a small vision in that the educational process limits to the transmission of specific and natural knowledge, just centered in the preservation and conservation of the nature.. The environmental perception of the educational ones revealed a content of lived experiences in relation to the environmental impacts associated to the patterns of the landscape local, conservation as meaning attribution for EEJ and environmental education jointly as proposed of use for EEJ and, the natural characteristics as main determinant of the preferences and quality landscapes. The results of that investigation facilitated the rising of the knowledge of the values area in the technical and human context, essential to determine the specific objectives of a Program of Education Environmental followed to a conservation unit.